A prospective study to investigate the impact of neutering bitches prepubertally or post-pubertally - Moxon, Rachel (2024)
Contradictory findings in the literature relating to the effects of timing of neutering on bitch behaviour and health make decision-making regarding neutering timing difficult. Most literature that examines the effect of neutering timing has used age rather than the onset of puberty as the primary variable. The aims of this study were to 1) conduct scoping reviews to identify and chart the evidence on the effects of neutering timing in relation to puberty on the behaviour and health of female dogs, and 2) conduct a prospective study to investigate the effects of neutering timing in relation to puberty on physical development, behaviour, progression through an assistance dog training programme and health for female dogs.